A evolução da organização e da localização espacial da agroindústria do leite no Rio Grande do Sul - Fiegenbaum, Joel (2013)
The present study aims to analyze the organization and location of dairy agro-industry in the state of Rio Grande do Sul between the years 1990-2010. This study seeks to assess the development of dairy agro-industry, in the aspects of industrial structure, production volume and location of the processing plant and capture raw. The theoretical references permeate the use of Commodity System Approach, the model structure-conduct-performance (SCP) dynamic strategies of Porter, the types of structure Guimarães and indicators Locational Quotient and Locational Gini. To conduct the study, we used the descriptive method and secondary data, followed by analysis of sectoral and geographical axis. In industry, discusses the structure of the agro-processing milk in Brazil and consequently the state of RS. In geographical axis seeks to determine the displacements of the primary production of milk, as well as the industrial processing of RS. The main results show that from 2002 to the expansion of demand for dairy products have as typologies of dairy industry in Brazil and RS three subgroups in the dairy industry, namely: a) subset of differentiated oligopoly among large firms sector b) subgroup of homogeneous oligopoly among firms of medium size, c) subgroup of competitive industry between firms marginal sector. Regarding performance, formulates the hypothesis that at the time the markets have become regionalized national (after the end of paradigm perishability milk) production units in RS when setting their prices through mark-up are watching what happens regarding the concentration level in Brazil. There is specialization and geographic concentration of production and processing of dairy in the northwestern state of RS.